2023
DOI: 10.3390/ph16020239
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Study on Vedolizumab Serum Concentration, Efficacy, and Safety after the Transition from Intravenous to Subcutaneous Vedolizumab in Inflammatory Bowel Disease Patients: Single-Center Experience

Abstract: Little is known about how the change from intravenous to subcutaneous vedolizumab in a real-life setting in inflammatory bowel disease patients on stable maintenance therapy affects clinical outcomes. We compared the data on vedolizumab serum trough concentration, efficacy, and safety prior to and six months after the switch from intravenous to subcutaneous vedolizumab. In total, 24 patients, 13 with ulcerative colitis (UC) and 11 with Crohn’s disease (CD), were included. Mean serum trough concentration of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…For patients with UC, Simple Clinical Colitis Activity Index (SCCAI) or PMS was used as the disease activity score in the studies, and clinical remission was defined as SCCAI ⩽2 25 , 26 or PMS ⩽1. 27 , 28 Changes in the SCCAI or PMS before and after the switch were reported in five studies, 24 28 with no observed significant differences except in one study that showed a decrease in the SCCAI. 25 Six studies 24 , 25 , 27 – 30 compared the proportion of patients in clinical remission before and after the switch, with no significant differences observed except in one study, which showed more patients in clinical remission at week 20 compared to the time of the switch.…”
Section: Effectiveness Of Sc Vdzmentioning
confidence: 96%
See 4 more Smart Citations
“…For patients with UC, Simple Clinical Colitis Activity Index (SCCAI) or PMS was used as the disease activity score in the studies, and clinical remission was defined as SCCAI ⩽2 25 , 26 or PMS ⩽1. 27 , 28 Changes in the SCCAI or PMS before and after the switch were reported in five studies, 24 28 with no observed significant differences except in one study that showed a decrease in the SCCAI. 25 Six studies 24 , 25 , 27 – 30 compared the proportion of patients in clinical remission before and after the switch, with no significant differences observed except in one study, which showed more patients in clinical remission at week 20 compared to the time of the switch.…”
Section: Effectiveness Of Sc Vdzmentioning
confidence: 96%
“…In clinical evaluations, the Harvey Bradshaw Index (HBI) was used as the disease activity score in all CD patients, and an HBI score of ⩽4 25 , 26 was defined as clinical remission. Changes in the HBI before and after the switch were reported in five studies, 24 28 none of which showed significant differences. For patients with UC, Simple Clinical Colitis Activity Index (SCCAI) or PMS was used as the disease activity score in the studies, and clinical remission was defined as SCCAI ⩽2 25 , 26 or PMS ⩽1.…”
Section: Effectiveness Of Sc Vdzmentioning
confidence: 99%
See 3 more Smart Citations